Re-calculation of the attenuation functions for Local Magnitude from the upgraded Central Weather Bureau Seismic Network in Taiwan - Zhuo-Kang Guan; Hao Kuo-Chen; Wei-Fang Sun (Terrestrial, Atmospheric and Oceanic Sciences, 2020)

(untitled)
The empirical attenuation functions for Local Magnitude (ML) currently used in Taiwan have been known for overestimated magnitudes around 0.2 compared with moment magnitude (MW) for shallow earthquakes (depths ≤ 35 km). Moreover, for deep earthquakes (depths > 35 km), ML (> 6) can be larger than MW around 0.5. Based on global observations and seismological theory, ML is equal to MW for magnitudes 4 - 6, whereas ML is smaller than MW for magnitudes > 6. This indicates that the attenuation functions for the Taiwan region need to be re-calculated. In this study, we used the new data set collected at the upgraded Central Weather Bureau Seismic Network (CWBSN24) from January 2012 to April 2019 and totally there are 692 events with ML ≥ 3 and 35228 amplitude data used for analysis. To accommodate the complicated tectonic environment in Taiwan, there are four attenuation functions, logA0(Δ), based on the focal depths and hypocentral distances, which are: